Assessing patient safety culture in obstetrics ward: A pilot study using a modified Manchester Patient Safety Framework in China - Li‐juan Wang; XiaoLing Wang; Min Zou; Li‐ping Jiang; Hui‐rong Ding (Wiley, 2023)
Abstract Aim The primary objective of this study was to assess the patient safety culture in a general hospital in Shanghai, China, through a modified Manchester Patient Safety Framework (MaPSaF). Design This study has a qualitative interview design. Data were collected through group interviews and analyses performed through content analysis. Methods The MaPSaF was translated into Chinese and used to assess the patient safety culture in a large general hospital in Shanghai, China. Group interviews using the MaPSaF were conducted with 15 nurses in the obstetric ward. Participants rated their safety practice individually on each of the nine MaPSaF safety culture dimensions. The dimensions and scores were then collectively discussed and a practice‐wide consensus score for each dimension was agreed. Discussions were recorded, transcribed and analysed to assess patient safety in the obstetric ward. Results It took about 2 hr to complete the discussion focusing on patients' safety employing the MaPSaF. Most participants recognized the process as acceptable and useful. The MaPSaF directed team discussion about patient safety issues and facilitated communication, prompting some practice changes. All participants responded positively to the discussion and perceived MaPSaF as a good safety culture assessment tool, with clear, comprehensive and understandable entries. The process demonstrated that the department of obstetrics in the hospital already had a positive patient safety culture, but certain areas were highlighted as still needing improvement. Based on participants' positive experience and perception of the MaPSaF, it can be concluded that there is potential benefit in its adaptation and use in obstetrics wards of Chinese hospitals. The MaPSaF has the potential to strengthen existing safety cultures and improve general safety through collaborative measures.